Models for project management in 2016 Olympic Games - Sousa, M. J. (2016)
The Olympic Games are the major sports event on the planet gathering people for all over the world and integrating several kind of resources that need to be managed in order to achieve efficiency and the sustainability of the event. The research question of this paper is “Which project management business model best fit a mega event like the 2016 Olympic Games?” The organizations which participate in the Olympic Games project management in Rio are under the pressure of external scenarios of uncertainty and also intense competition and internally the organizations that manage all the Olympic resources need to deal with limitations of costs and time – the business model adopted can help to achieve a major success of the event. According to studies made on the past Olympics Project Managers face various challenges and the models adopted can made an integration of various and disperse project management tools. The main finding of this research is that project management maturity models benefits management approaches and reinforce the definition and the use of strategic plans enhancing the control techniques of project management and also the sustainability model is necessary to orchestrate the successful completion of a project with the amplitude of Olympic Games.